Identidad cultural en estudiantes del 3° grado de la I.E. “Víctor Herrera Delgado” de Tacabamba como promotor del Turismo Cultural. - Rojas Tenorio, Analy (2019)
The present work called CULTURAL IDENTITY IN 3RD GRADE STUDENTS OF THE I.E “VÍCTOR HERRERA DELGADO” FROM TACABAMBA AS PROMOTER OF CULTURAL TOURISM, has as objective Recognize and describe the elements of the Cultural Identity of the third year students of the secondary level who could be the promoter of cultural tourism. _x000D_ The recognition of the cultural heritage divided into: Beliefs, customs, values of the students of Tacabamba, allow identifying the most representative icons that they possess such as: Crafts, gastronomy, music, language and religion. The value of the cultural identity of the students allows laying the foundations for the development of cultural tourism in the District of Tacabamba. _x000D_ The analysis of the sociocultural aspect of the students of the third grade of secondary of the IE "Victor Herrera Delgado" allows to demonstrate that this contributes to the development of the local cultural tourism of the communities of influence, generating the recognition of the material and immaterial heritage of the destination among the settlers, as well as increasing the cultural identity of the inhabitants of the area by determining representative icons of their culture. _x000D_ In order to obtain the data, the following activities have been carried out; application of the technique of direct observation in the province; interview aimed at key informants, surveys of students and the technique of signing for the inventory of cultural heritage, as well as instruments such as survey questionnaire and interview, field notebooks and cameras. Both the techniques and the instruments allowed us to obtain adequate information for the preparation of this report.